2021
DOI: 10.3389/fnbeh.2020.601111
|View full text |Cite
|
Sign up to set email alerts
|

Impact of High Fat Diet and Ethanol Consumption on Neurocircuitry Regulating Emotional Processing and Metabolic Function

Abstract: The prevalence of psychiatry disorders such as anxiety and depression has steadily increased in recent years in the United States. This increased risk for anxiety and depression is associated with excess weight gain, which is often due to over-consumption of western diets that are typically high in fat, as well as with binge eating disorders, which often overlap with overweight and obesity outcomes. This finding suggests that diet, particularly diets high in fat, may have important consequences on the neurocir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 216 publications
(248 reference statements)
0
5
0
Order By: Relevance
“…We and others have reported that exposure to high‐energy diets or “western diet formulas,” such as a cafeteria diet, favors aberrant behaviors in offspring, including depression‐like (de la Garza et al, 2019; Trujillo‐Villarreal et al, 2021), addiction‐like (Camacho et al, 2017; Cruz‐Carrillo et al, 2020), asocial‐like behaviors (Maldonado‐Ruiz et al, 2022), cognitive impairments (Lépinay et al, 2015; Létondor et al, 2016; Manduca et al, 2017) and ADHD (Buss et al, 2012; Chen et al, 2014; Godfrey et al, 2017; Sanchez et al, 2018). These evidences propose that excessive consumption of a high‐energy diet might have significant effects on mental health in children's, adolescents and adults (Baker et al, 2017; Coker et al, 2021; Lof et al, 2022; Melo et al, 2019; Muscaritoli, 2021; Ortiz‐Valladares et al, 2021). As a result of the multifactorial pathogenesis in mental disorders causal links between dietary suppliers on mental health have been hard to establish, in part, based on food formulas provide natural energy substrates for brain energy metabolism.…”
Section: Diet Modulates Ceramides Metabolism and Susceptibility To Ps...mentioning
confidence: 99%
See 1 more Smart Citation
“…We and others have reported that exposure to high‐energy diets or “western diet formulas,” such as a cafeteria diet, favors aberrant behaviors in offspring, including depression‐like (de la Garza et al, 2019; Trujillo‐Villarreal et al, 2021), addiction‐like (Camacho et al, 2017; Cruz‐Carrillo et al, 2020), asocial‐like behaviors (Maldonado‐Ruiz et al, 2022), cognitive impairments (Lépinay et al, 2015; Létondor et al, 2016; Manduca et al, 2017) and ADHD (Buss et al, 2012; Chen et al, 2014; Godfrey et al, 2017; Sanchez et al, 2018). These evidences propose that excessive consumption of a high‐energy diet might have significant effects on mental health in children's, adolescents and adults (Baker et al, 2017; Coker et al, 2021; Lof et al, 2022; Melo et al, 2019; Muscaritoli, 2021; Ortiz‐Valladares et al, 2021). As a result of the multifactorial pathogenesis in mental disorders causal links between dietary suppliers on mental health have been hard to establish, in part, based on food formulas provide natural energy substrates for brain energy metabolism.…”
Section: Diet Modulates Ceramides Metabolism and Susceptibility To Ps...mentioning
confidence: 99%
“…cognitive impairments(Lépinay et al, 2015;Létondor et al, 2016;Manduca et al, 2017) and ADHD(Buss et al, 2012;Chen et al, 2014;Godfrey et al, 2017;Sanchez et al, 2018). These evidences propose that excessive consumption of a high-energy diet might have significant effects on mental health in children's, adolescents and adults(Baker et al, 2017;Coker et al, 2021;Lof et al, 2022;Melo …”
mentioning
confidence: 99%
“…The contradictory findings seem to be due the exposure length of alcohol (acute or chronic), mode of electrophysiologic recording, and the subregion of the CeA. Additionally, diet composition may play an important role in regulating alcohol modulation of CeA neurotransmission ( Coker et al, 2020 ; Mahajan et al, 2021 ).…”
Section: Glutamatergic Transmissionmentioning
confidence: 99%
“…However, the involvement of metabolising enzymes, that are primarily expressed in the liver, does not address why many people choose to drink alcohol and why alcohol use may develop into an addiction. It is widely understood that the decision to drink alcohol is modulated by regions of the brain, that include the hypothalamus and that addiction involves regions that include the nucleus accumbens [8 , 9] . Aside from the afore mentioned metabolic genes, the majority of genetic risk seems to be spread amongst a large number of variants each with small effects, a known common feature of the genetics of complex diseases [10] .…”
Section: The Problem At Handmentioning
confidence: 99%
“…Based on these observations it is likely that the greatest burden of AUD causing SNPs do not lie within the coding regions of genes but within the unknown, and enigmatic, non-coding genome. Consequently, the main aim of the current review will not be to explore the known genetics or neuroscience of AUD in any depth, a subject which has been well reviewed in a number of other publications [8 , 9] , but to briefly and critically appraise what we know about the information sources contained in the “non-coding” genome that are important in health, what techniques are currently used to understand the role of the non-coding genome in alcohol intake and what we need to do in the future to better understand its biology.
Fig.
…”
Section: The Problem At Handmentioning
confidence: 99%